Barriers to Referral for Elevated Blood Pressure in the Emergency Department and Differences Between Provider Type. Issue 3 (13th January 2015) - Souffront, Kimberly; Chyun, Deborah; Kovner, Christine
<x xml:space="preserve">Abstract</x> A multidisciplinary sample of emergency department providers across the United States (n=450) were surveyed to identify barriers to referral for elevated blood pressure (BP) in the emergency department and differences between provider type. Registered nurses reported less knowledge of stage I hypertension (P=.043) and prehypertension (P<.01); were less aware of definitions for hypertension (P<.001); reported more difficulty in caring for patients who are asymptomatic (P=.007); required financial compensation to refer (P=.048); and perceived that BP referrals are influenced by the medical director (P<.001). Medical doctors reported more skills to refer (P=.008) and time as a barrier (P=.038). Physician assistants were more likely to report patients are not aware of health benefits (P=.035), doubted their concern for their BP (P=.023), and felt emotionally uncomfortable when referring (P=.025). Despite these differences, there was no significant difference between provider type and referral rates.